Criação de um jogo de tabuleiro inserido em um universo fantástico - Kumoto, Rafael Togo (2011)
This work presents the development of a board game projected for the Brazilian market and represents, at first, the results of a study concerning games working behavior and the process of interaction between players. It is intended to consumers used to national products, but with no contact with the big production from countries like Germany and USA. This study dedicates to analyze and collect national and international games mechanics, and compare to the main user’s profile. At a second moment, it documents a long testing sequence held aiming the creation of a game system consistent with its theme, focused on the pirates’ folklore.